Analysis and prediction of immune cell infiltration characteristics in COPD: Folium isatidis and its active ingredients are able to combat lung lesions caused by COPD by correcting immune cell infiltration - Wang, Faqin; Zhang, Weichen; Huang, Yujie; Hou, Xianbang; He, Liwei; Xu, Huiqin (Frontiers in Medicine, 2025)
ObjectiveAs a respiratory disease, chronic obstructive pulmonary disease (COPD) has become a common fatal disease worldwide. We aimed to screen active traditional Chinese medicines (TCMs) for the treatment of COPD by COPD-related transcriptome gene chip analysis and verify their therapeutic activity for COPD.MethodsWe used bioinformatics analysis to predict potential therapeutic TCMs based on the immune cell infiltration characteristics in COPD. Further, BALB/c female mice were divided into different treatment groups to investigate the effect of indirubin (IDR) and FI on COPD. After 12 weeks of intranasal lipopolysaccharide instillation and passive smoking, we started giving drug treatment to mice, including distilled water (control and model groups), dexamethasone, IDR and FI. The lung function, visceral index, degree of lung tissue damage, and immune cell infiltration were assessed.ResultsWe identified 109 differential genes, 22 immune cells, and 50 TCMs associated with the alleviation of COPD. The in vivo experimental results showed that IDR and FI had protective effects against lung injury in mice and could inhibit COPD. The mechanism of this effect may be related to their ability to regulate the proportion and distribution of immune infiltration of B lymphocytes, CD4+ and CD8+ T lymphocytes, Treg cells, NK cells, myeloid-derived suppressor cells, and eosinophils.ConclusionIDR and FI can ameliorate disease development in COPD model mice by regulating immune cell infiltration. This offers an experimental groundwork for delving deeper into the mechanisms through which TCMs impact COPD treatment and for identifying possible therapeutic drugs for COPD.